Os múltiplos processos de construção da autonomia do movimento zapatista - Juan Diez (Universidade do Vale do Rio dos Sinos (UNISINOS), 2012)
Over years of struggle, the Zapatista movement not only managed to place the issue of autonomy at the center of political debate, particularly in relation to indigenous people, but at the same time the processes of autonomy building have become the cornerstone of its political project and its own dynamics. This article analyzes the autonomous indigenous processes that are taking place in the communities in Chiapas since the Zapatista uprising, as well as a broader discussion on autonomy from the state and political parties that was encouraged by the Zapatistas from the very beginning. Both processes are addressed from the perspective of the Zapatista movement as a whole, taking into account not only the Zapatista Army of National Liberation, but also indigenous communities and many organizations, groups, and individuals who fight alongside the Zapatistas in Mexico. Thus, the emphasis is on the necessary coordination and interaction of these processes and the different actors involved, avoiding analyzing them as isolated phenomena.